Penyelesaian Kasus Perceraian di Pengadilan Agama Secara E-Court Berdasarkan Perma Nomor 7 Tahun 2002 - Fauziah Lubis; Nur Aisah; Rifqi Althaaf Masaid; M. Farhan Damanik; Siti Nurul Latifah; Fitri Nabila (Pusat Riset dan Inovasi Nasional, 2025)
this journal is written to examine divorce cases which are complex social problems and often have psychological and economic impacts on families. In Indonesia, the Religious Court (PA) plays an important role in resolving divorce disputes. Over time (MA RI) has sought to improve the efficiency and transparency of judicial services through the implementation of a system that regulates the application of this electronic system in various cases, including divorce cases. This study is important to evaluate the extent to which the implementation of e-Court in resolving divorce cases in PA is in accordance with the PERMA, identify the obstacles faced, and provide recommendations for improving and optimizing the system. It is hoped that this study can contribute to improving services in the courts in handling divorce cases and supporting the realization of simple, fast, and low-cost access to justice.